Met125 is essential for maintaining the structural integrity of calmodulin’s C-terminal domain - Sarah E. D. Nelson (Nature Portfolio, 2020)
Abstract We have used NMR and circular dichroism spectroscopy to investigate the structural and dynamic effects of oxidation on calmodulin (CaM), using peroxide and the Met to Gln oximimetic mutations. CaM is a Ca2+-sensitive regulatory protein that interacts with numerous targets. Due to its high methionine content, CaM is highly susceptible to oxidation by reactive oxygen species under conditions of cell stress and age-related muscle degeneration. CaM oxidation alters regulation of a host of CaM’s protein targets, emphasizing the importance of understanding the mechanism of CaM oxidation in muscle degeneration and overall physiology. It has been shown that the M125Q CaM mutant can mimic the functional effects of methionine oxidation on CaM’s regulation of the calcium release channel, ryanodine receptor (RyR). We report here that the M125Q mutation causes a localized unfolding of the C-terminal lobe of CaM, preventing the formation of a hydrophobic cluster of residues near the EF-hand Ca2+ binding sites. NMR analysis of CaM oxidation by peroxide offers further insights into the susceptibility of CaM’s Met residues to oxidation and the resulting structural effects. These results further resolve oxidation-driven structural perturbation of CaM, with implications for RyR regulation and the decay of muscle function in aging.